Decoupling of impulsive differential equations - Reinfelds, Andrejs (Mathematical Modelling and Analysis, 1997)
“Decoupling of impulsive differential equations”Mathematical Modelling Analysis, 2(1), p. 130-137.First Published Online: 14 Oct 2010